Synergetics: The Path from General Systems Theory to Self-Organization - Rizaev Ilhom Imomalievich (Global Scientific Publishing, 2023)
This article provides a historical overview of the evolution of synergetics as a scientific idea, with an emphasis on its development as a modern general methodology. The author notes that synergetics is the successor to methodological traditions formed within the framework of works on cybernetics and the systems approach. The article indicates that the main foundations of modern synergetics were laid in the general theory of systems and cybernetics. In addition, the basic principles of systems theory are discussed, based on analogies with living organisms, which played an important role in the development of synergetics
Keywords: historical retrospective; synergetics; methodology